2001
DOI: 10.1089/15209150152607123
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Effect of the Use of Computer-Based Systems on the Metabolic Control of Patients with Diabetes Mellitus

Abstract: The purpose of this study was to evaluate, through a meta-analysis study, whether the use of computer-based systems reported in the literature improves the metabolic control of diabetic patients. On the retrieved papers, a set of meta-analysis studies were performed: first the difference of HbA1c between cases and controls at follow-up was evaluated (sign test); then the difference between cases and controls in the total variation of HbA1c from the beginning to the end of the trial was considered (method of ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 21 publications
(65 reference statements)
3
32
0
1
Order By: Relevance
“…Therefore, it is conceivable that the concerted efforts of professional organizations and clinicians at improving glycemic control are bearing fruit. A variety of approaches can improve glycemic control (15)(16)(17)(18)(19)(20). Learning whether these approaches or other factors may have positively impacted the recent trends in glycemic control could provide important lessons for effecting further improvements in glycemic control in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is conceivable that the concerted efforts of professional organizations and clinicians at improving glycemic control are bearing fruit. A variety of approaches can improve glycemic control (15)(16)(17)(18)(19)(20). Learning whether these approaches or other factors may have positively impacted the recent trends in glycemic control could provide important lessons for effecting further improvements in glycemic control in the future.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28][29][30] This project, however, differs from prior studies because it was nurse-based, the recruitment process did not target patients with only poor glycemic control, and computer experience or computer literacy was not required for eligibility. Additionally, this study also disproves the myth that seniors will not be attracted to the Internet as a way of communication.…”
Section: Discussionmentioning
confidence: 99%
“…At least 2 other metaanalyses also found that the use of computer-based systems for patients with diabetes could be an effective means of improving metabolic control. 66,67 Healthcare executives and policymakers would probably like to obtain additional information about costs and more meticulous long-term data on patient acceptance and clinical utilization of the systems, because they are likely to be considering a purchase. Future studies should also include cost calculations of computerized interventions in diabetes care.…”
Section: Discussionmentioning
confidence: 99%